1983
DOI: 10.1159/000466074
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Associated IgM Levels in Thrombocytopenia

Abstract: Platelet-associated IgG (PAIgG) and IgM (PAIgM) levels were quantitated in patients with thrombocytopenias of various etiologies. 32 of 34 patients with immune thrombocytopenia had elevated PAIgG, 8 of the 34 patients had elevated PAIgM levels. Only 1 patient suffering from immune thrombocytopenia had elevated PAIgM with normal PAIgG levels. Elevated PAIgM was most often associated with elevated PAIgG except for the following: 2 patients with lymphoproliférative disorders, 1 patient with heparin-induced thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
1985
1985

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Using an immunofluorescent technique, von dem Borne et al (1980) first reported that IgM autoantibodies may occur singly (in 5%) or in conjunction with IgG antibodies (in 24%) in their series of patients with AITP. Pawha et al (1983) reported similar results using a different technique. In contrast, however, Nel et al(l983) found elevated PAIgM levels in a much higher proportion of patients, i.e.…”
Section: Discussionmentioning
confidence: 58%
“…Using an immunofluorescent technique, von dem Borne et al (1980) first reported that IgM autoantibodies may occur singly (in 5%) or in conjunction with IgG antibodies (in 24%) in their series of patients with AITP. Pawha et al (1983) reported similar results using a different technique. In contrast, however, Nel et al(l983) found elevated PAIgM levels in a much higher proportion of patients, i.e.…”
Section: Discussionmentioning
confidence: 58%
“…In these cases, the deposition of C3 could result from the presence of anti-platelet antibodies of the IgM class that are known to activate complement more efficiently than most IgG antibodies. Indeed, several investigators have recently observed increased amounts of IgM on the platelets of some patients with ITP (15)(16)(17)(18)(19)(20)(21)(22). Therefore, we sought to determine if complement-fixing IgM anti-platelet antibodies are, in fact, demonstrable in ITP and could account for the presence of C3 on the platelets of some of these patients.…”
Section: Introductionmentioning
confidence: 99%